Harnessing Project Identity and Safety Norms to Promote Construction Workers’ Safety Behavior: Field Intervention Study - Bae, Juhyeon; Choi, Byungjoo; Krupka, Erin; Lee, Sang Hyun (Journal of Construction Engineering and Management, 2025)
The importance of workers’ social identity in shaping their safety behaviors has become increasingly acknowledged. Among various social identities (e.g., workgroup, trade, etc.), improving project identity stands out as particularly impactful; it not only promotes safer behaviors among workers but also establishes a shared identity that unites all project members, thereby enhancing their sense of belonging. However, existing management strategies, primarily designed for traditional, long-term organizations, often require substantial managerial efforts to build and maintain high-quality management-employee interactions or organizational reputation. Such strategies may be less effective and economically impractical in the temporary nature of construction projects, suggesting a notable gap in management strategies that effectively foster workers’ project identity to enhance safety behaviors. To fill this knowledge gap, the authors aim to develop and evaluate affordable and easy-to-implement managerial interventions that foster workers’ project identification and safety behaviors. Drawing on social identity theory, the authors designed project identity-promoting messages and symbols that could be easily embedded into everyday items, such as posters and T-shirts. To evaluate their effectiveness, longitudinal field experiments were conducted, gathering 124 self-reported surveys on project identification and safety behavior from 31 workers before and after the interventions at two separate construction sites over three months. The survey data were analyzed using repeated measures (RM) ANOVA analysis to examine changes before and after the intervention. The results indicate significant improvements in both affective and behavioral dimensions of project identification, as well as in safety participation, demonstrating the potential of social identity-based interventions in improving workers’ safety behaviors and project identification. This study contributes to the body of knowledge on construction organizations and construction safety by developing and evaluating practical managerial interventions based on social identity theory, which enhance construction workers’ project identification and safety behavior.
Keywords: Construction workers; Intervention studies; Management strategies; Project identification; Safety behavior; Social identity; Social identity theories; Worker safety; Workers'; Workgroups